A Simple Dynamic Signal Analyzer Virtual Instrument To Monitoring and Control Airflow Temperature - Asmara Yanto; Anrinal Anrinal; Ryan Adi Pratama (Jurnal Teknik Mesin (JTM), 2016)
This work aims to present a Dynamic Signal Analyzer Virtual Instrument (DSA-VI) for monitoring and control the airflow temperature in a prototype of air duct. Here, the DSA-VI has developed by using LabVIEW software and Arduino UNO.  To investigate the performance of DSA-VI, an experiment has performed to monitoring and control airflow at settling temperature, 40oC, 50oC, and 60oC, respectively by using the DSA-VI. By assuming that an airflow temperature control system as the first order system, the time constant (t) should be inspected as one of the system characteristics. The testing at the settling and surrounding temperatures (Tsp and T0) are 40oC and 28.81oC respectively, obtained value of t is 7.49 s; at Tsp and T0 are 50oC and 29.88oC respectively, obtained value of t is 11.35 s; and at Tsp and T0 are 60oC and 28.81oC respectively, obtained value of t is 19.54 s. By using DSA-VI, the value of t at the transient response can be evaluated. At the steady state response, the airflow temperature has controlled well with the steady state error less than ± 2.5 %.